Teksty farmaceutyczne i dyskurs farmaceutyczny: definicje, specyfika i krótki przegląd pola badawczego - Grabowski, Łukasz (Języki specjalistyczne w komunikacji interkulturowej, 2020)
This chapter aims to familiarize readers with the specificity of pharmaceutical discourse, including its spoken and written text varieties. I paid particular attention to two issues. Firstly, pharmaceutical discourse and pharmaceutical texts are often classified by researchers into broader category of medical or biomedical discourse. Second, pharmaceutical discourse is not autonomous as it is also permeated with medical, legal, academic and other discourses. Next, pharmaceutical discourse was described in greater detail using descriptive models proposed by Bhatia (2004) and Gunnarson (2009). Finally, a selection of research studies, including linguistic and interdisciplinary ones, conducted on certain pharmaceutical text types and genres, both spoken and written, were presented to provide a more comprehensive overview of the research field.